Active spoof plasmonics: from design to applications. (11th November 2021) - Ren, Yi; Zhang, Jingjing; Gao, Xinxin; Zheng, Xin; Liu, Xinyu; Cui, Tie Jun
Abstract: Spoof plasmonic metamaterials enable the transmission of electromagnetic energies with strong field confinement, opening new pathways to the miniaturization of devices for modern communications. The design of active, reconfigurable, and nonlinear devices for the efficient generation and guidance, dynamic modulation, and accurate detection of spoof surface plasmonic signals has become one of the major research directions in the field of spoof plasmonic metamaterials. In this article, we review recent progress in the studies on spoof surface plasmons with a special focus on the active spoof surface plasmonic devices and systems. Different design schemes are introduced, and the related applications including reconfigurable filters, high-resolution sensors for chemical and biological sensing, graphene-based attenuators, programmable and multi-functional devices, nonlinear devices, splitters, leaky-wave antennas and multi-scheme digital modulators are discussed. The presence of active SSPPs based on different design schemes makes it possible to dynamically control electromagnetic waves in real time. The promising future of active spoof plasmonic metamaterials in the communication systems is also speculated.